Teledermatology: one application of telemedicine - Perednia, D A; Brown, N A (Bulletin of the Medical Library Association, 1995)
Telemedicine can be defined as the use of telecommunications technologies to provide medical information and services. This field has recently begun a period of explosive growth. Oregon's teledermatology program within the National Library of Medicine's high-performance computing and communications initiative is designed to generate much-needed basic and clinical research information about one specific telemedicine application. The background of this program is discussed, and the research objectives are described.